Effects of biogenic volatile organic compounds and anthropogenic NOx emissions on O3 and PM2.5 formation over the northern region of Thailand - Uttamang, Pornpan; Janta, Radshadaporn; Bran, Sherin Hassan; Macatangay, Ronald; Surapipith, Vanisa; Tala, Wittaya; Chantara, Somporn (Frontiers in Environmental Science, 2023)
It is questionable as to whether the forests could also be a major source of air pollutions in the northern region of Thailand where greater than 60 % of the region is covered by forests. Herein we investigated the effects of biogenic volatile organic compounds (BVOCs) emitted from plants – isoprene in particular and anthropogenic NOx emissions on ground-level ozone (O3) and fine particulate matters (PM2.5) formation. By using the isoprene observations over the northern region of Thailand, isoprene adjustment factors for model simulations were estimated. The weather research and forecasting model coupled with a chemistry model (WRF-Chem Model) was performed to simulate four scenarios including baseline, noBio, modiBio and modiAntho simulations. The modeling results over the northern region of Thailand indicate that changes in BVOCs were sensitive to the formation of O3 rather than changes in NOx emissions, while BVOCs had a direct relationship to glyoxal and SOA of glyoxal. In June, decreases in anthropogenic NOx emissions by 40 % led to PM2.5 reductions, which corresponded to a 100 % reduction in BVOCs. While higher PM2.5 reductions were found to be caused by anthropogenic NOx reductions in November, small increases in PM2.5 were observed over the area near a power plant located in Lampang Province. Although BVOC emissions over northern Thailand effectively contributed only 5.3 to 5.6 % of the total concentrations of PM2.5, this study can help to recognize the impact of biogenic and anthropogenic emission sources on SOA and surface ozone in this area.